Emerging Role of Women in Household Food Access in Nyamira North Sub County, Kenya - Auya , Samwel (African Journal of Education,Science and Technology (AJEST), 2023)
Food insecurity is a contemporary challenge afflicting a number of households in developing countries. In Kenya for instance, households that have traditionally relied on their farms for food are currently experiencing reduced food production occasioned by reduced land sizes due to successive land sub-division and application of traditional farming methods. With reduced household food production and subsequent household food insecurity, the traditional cultural belief that men are the sole breadwinners in households’ food requirements might not hold water. This is due to the concerted efforts by family members to work towards the realization of household food needs. Therefore, this study investigated the role of women in enhancing household food access in Nyamira North Sub County. Specifically, the study examined the emerging role of women in household food access and how the emerging role has influenced social life in households. Anchored on social role theory, the study employed focus group discussions and in-depth interviews to gather data that was analyzed by qualitative techniques. The study revealed that land-use decision-making, involvement in food production on farms, and engagement in manual work to generate income for household food provision are the emerging roles of women in household food access in the study area. On how the emerging role has influenced social life in households, the study established that women’s role in household food access in the study area has led to the breakdown of families, diminished respect for husbands, and change in household power relations. The study concludes that women have taken an active role in household food provision although this has fueled social change in household social life. The study recommends that policy formulation by relevant authorities is paramount to help upscale and strengthen women’s participation in household food access and foster synergy within households with regard to household food access.